COVID-19: The imposter in our emergency department - Wilson, William (Research and Humanities in Medical Education, 2021)
As the world battles COVID-19, talks are rife about vaccine distribution and health policy overhauls. Amongst all this mayhem a section of patients suffers silently. The patients with chronic systemic diseases requiring regular care at the hospital for follow-ups and dialysis are getting lost in the crowd of COVID suspects. This paper narrates the harrowing ordeal of a patient shunted across hospitals all because of a fever, and in the end it discloses her eventual diagnosis.